2017
DOI: 10.1038/srep41936
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide Receptor B modulates the proliferation of the cardiac cells expressing the Stem Cell Antigen-1

Abstract: Brain Natriuretic Peptide (BNP) injections in adult “healthy” or infarcted mice led to increased number of non-myocyte cells (NMCs) expressing the nuclear transcription factor Nkx2.5. The aim of this study was to identify the nature of the cells able to respond to BNP as well as the signaling pathway involved. BNP treatment of neonatal mouse NMCs stimulated Sca-1+ cell proliferation. The Sca-1+ cells were characterized as being a mixed cell population involving fibroblasts and multipotent precursor cells. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…1A). This protocol from our previous studies demonstrated that BNP injections (first intraventricular and then intraperitoneal) reduced heart remodelling and increased Sca-1 + cell numbers 16,26 . However, as BNP modulates the function of different organs (kidneys, vessels, pancreas), its effect on hearts could be indirect.…”
Section: Bnp Direct Action On Cardiac Non-myocyte Cells After Intrapementioning
confidence: 98%
See 3 more Smart Citations
“…1A). This protocol from our previous studies demonstrated that BNP injections (first intraventricular and then intraperitoneal) reduced heart remodelling and increased Sca-1 + cell numbers 16,26 . However, as BNP modulates the function of different organs (kidneys, vessels, pancreas), its effect on hearts could be indirect.…”
Section: Bnp Direct Action On Cardiac Non-myocyte Cells After Intrapementioning
confidence: 98%
“…Non-myocyte cells (NMCs) were isolated from the hearts of neonatal C57BL/6, NPR-A KO or NPR-B KO pups (1-2 days) as previously described 16,26 and were cultured in medium composed of MEM Alpha (Gibco 32571-028), 10% FBS, 100 U/ml penicillin G, 100 µg/ml streptomycin with or without BNP (5 µg/ml) up to confluence (i.e., 10-11 days). Adult cardiac NMCs were isolated from adult C56BL/6 mice (6-8 weeks old) by digesting adult ventricles in buffer containing 1 mg/ml collagenase IV (Gibco 17104-019) and 1.2 mg/ml dispase II (Sigma, D4693) and were cultured in EGM™-2 Endothelial Cell Growth Medium-2 BulletKit (Lonza, CC-3162) supplemented with 15% fetal calf serum (FCS) (invitrogen Corp) with or without BNP (5 µg/ml) up to confluence (i.e., 5-10 days).…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…However, some groups [ 38 , 52 , 53 , 54 ] reported that plasma BNP levels are elevated in patients with cancer and suggested that these increases are due to the cardiac response to cancer-related inflammation. Indeed, BNP is upregulated at the transcriptional and translational levels by pro-inflammatory cytokines in myocardiocytes [ 55 ] and patients with hematologic malignancies have elevated levels of N-terminal –proBNP, related to a possible myocardium response to the setting of the cancer [ 56 , 57 ]. Serum levels of N-terminal pro- C-type NP are associated with bone formation activity in patients with multiple myeloma [ 58 ], and act on mice lung fibroblasts to reduce pulmonary fibrosis [ 59 ].…”
Section: Natriuretic Peptides and Cancermentioning
confidence: 99%